Analisis Kepribadian Tokoh Utama Dalam Cerita Pendek Lamb to the Slauher Karya Roald Dahl - Rahmawati, Ismi (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study aims to explain the main character in the short story Lamb to the Slaughter by Roald Dahl. The attitude and characteristics of the main character Mrs. Mary Maloney and how the main character's personality is described in the story. The research uses several theories, such as character and characterization theory. personality theory. Character is a habit of the process of action that is carried out by individuals repeatedly, and characterization refers to the description of the author and the development of the character (Griffith, 1982: 29). There are three categories of characters according to William Kenney (1966:27), based on their function: characters are divided into several types, namely: main characters, secondary characters, and supporting characters. Characterization is the way a writer displays the personality of a character. Both direct and indirect characterizations are used to express characteristics. There are two types of characterization methods: direct and indirect which refer to research results. Keywords: Characteristics; Main Figures; Short Story.